ANALISIS HUKUM EKONOMI ISLAM TERHADAP MEKANISME JUAL BELI ONLINE SISTEM DROPSHIPPING (Studi Kasus di Diza_Olshop Kecamatan Sukorejo Kabupaten Ponorogo) - Tri Mulyani; Suad Fikriawan; Nafiah Nafiah (Social Science Academic, 2023)
Buying and selling online dropshipping system is an online buying and selling system that is carried out through social media, aiming to make it easier for sellers and buyers. In the mechanism of buying and selling online, the dropshipping system found several problems, such as the law on the goods being traded, there is an element of ambiguity. Buying and selling like this will be detrimental to both the buyer and the seller because the seller who acts as a dropshipper will find it difficult when the buyer complains about the incompatibility of the goods he ordered. This thesis reports the results of the research, with the formulation of the problem: (1) What is the mechanism for buying and selling online with the dropshipping system at Diza_Olshop, Sukorejo District, Ponorogo Regency? (2) Why does the online buying and selling mechanism with the dropshipping system often cause problems at Diza_Olshop? (3) How is the analysis of Islamic Economic Law on buying and selling online with the dropshipping system at Diza_Olshop?. This research approach is a type of field research. Data collection techniques with observation, interviews and documentation. Based on the results of data analysis it can be concluded that: (1) The online buying and selling mechanism with a dropshipping system at Diza_Olshop is based on a greeting contract, (2) It often causes problems at Diza_Olshop due to internal factors. (3) Analysis of Islamic Economic Law, buying and selling online with the dropshipping system at the Diza_Olshop is permissible if it is in accordance with the salam sale and purchase contract and does not contain elements of gharar, usury, other evils and aims to help each other.